Clinical Implementation of Cone Beam Computed Tomography-Guided Online Adaptive Radiation Therapy in Whole Breast Irradiation - Koen J. Nelissen, MS; Wilko F.A.R. Verbakel, PhD; Judith G. Middelburg–van Rijn, MD; Barbara L.T. Rijksen, MD; Marjan A. Admiraal, PhD; Jorrit Visser, PhD; Jessica van der Himst; Karin N. Goudschaal, MS; Ewa Bucko; Ben J. Slotman, MD; Angelique R.W. van Vlaenderen, MS; Desiree H.J.G. van den Bongard, PhD, MD (Advances in Radiation Oncology)
Purpose: In postoperative breast irradiation, changes in the breast contour and arm positioning can result in patient positioning errors and offline replanning. This can lead to increased treatment burden and strain on departmental logistics because of the need for additional cone beam computed tomography (CBCT) images or even a new radiation therapy treatment plan (TP). Online daily adaptive radiation therapy (oART) could provide a solution to these challenges. We have clinically implemented and evaluated the feasibility of oART for whole breast irradiation. Methods and Materials: Twenty patients treated with postoperative whole breast right irradiation (5 × 5.2 Gy) were included in BREAST-ART, a prospective single-arm trial. The dosimetry of the reference TP calculated on the daily anatomy and adaptive TP were compared. Duration of the oART workflow, in-house satisfaction questionnaires, and acute toxicity (National Cancer Institute Common Terminology Criteria for Adverse Event v5.0) were collected. The oART workflow was evaluated by investigating the impact of manual corrections of influencer and target contours on treatment time and quality. Results: In the first 17 patients (85 fractions), the on-couch time, ie, the time between the end of CBCT1 and CBCT3, was a median of 13.8 minutes (range, 11–25). Retrospective evaluation of the use of the influencer (ie, breast) in 4 patients (20 fractions) and manual correction of the most cranial and caudal target contours (ie, 4 mm) in 10 patients (36 fractions) was done. This resulted in a reduced on-couch time in the last 3 clinical patients to a median of 13.0 minutes (range, 11–19). No grade 3 or higher toxicity was observed, and 19 of 20 patients indicated that they preferred the same treatment again. Skin marks for patient positioning during treatment were no longer necessary. Conclusions: This study showed the feasibility, challenges, and practical solutions for the implementation of oART for breast cancer patients. Future work will focus on more complex breast indications, such as whole breast, including axillary nodes, to further investigate the benefits and challenges of oART in breast cancer.